PENYELENGGARAAN PAUD TERINTEGRASI LAYANAN KESEHATAN DAN GIZI DALAM LAYANAN MUTU PEMBELAJARAN PAUD DI POSYANDU KABUPATEN GORONTALO - Halidu, Salma (2011)
The problem of this research is about "What extent the implementation of Integrated Early Childhood Care and Nutrition in Early Childhood Learning Quality in integrated health?". The purpose of this study were (1) describe how the implementation of integrated early childhood health and nutrition services to improve the quality of early childhood learning services at neighborhood health center district of Gorontalo. (2) understand the barriers faced in the implementation of integrated early childhood health and nutrition services in improving the quality of learning services at neighborhood health center in the district of Gorontalo. And (3) know how the quality of learning services in the implementation of integrated early childhood health and nutrition services at neighborhood health center district of Gorontalo. Concept as fundamental in this research is the holistic nature of early childhood, the nature of Posyandu, the nature of the quality of teaching, the nature of health and nutrition, and characteristics of early childhood. This study used a qualitative approach, analysis, data collection techniques used were observation, documentation and interviews conducted on the implementation of integrated early childhood. The data analysis technique used is descriptive analysis technique citizens and governments. The results of this study indicate that (1) Implementation of integrated early childhood health and nutrition services, that in the planning, implementation and evaluation have been implemented, (2) barriers that exist both external and internal which occur either from the tutor manager, parents of the tutors themselves are issues such time there meetings to attend so that the learning process is not going according to planned, and also the distribution of time that must be scheduled by management in its involvement in both the management and monitoring of the implementation of cost issues and the presence of parents in the participation of both proposing a plan for the development of Post ECD, and (3) Quality of service learning students' views of developments both in terms of cognitive development, language, social, moral, motor and art tutors have a good responsibility. Based on research data education and experience factors can increase the ability of cadres, then the lack of parental involvement in the participation of more integrated organization of early childhood socialization for the sake of improvement while to get a more adequate facilities necessary for the observer to negotiate management education. Masalah penelitian ini yaitu tentang "Sejauhmana penyelenggraan PAUD Terintegrasi Layanan Kesehatan dan Gizi dalam Mutu Pembelajaran PAUD di Posyandu?". Tujuan penelitian ini adalah (1) mendeskripsikan bagaimana penyelenggaraan PAUD terintegrasi dengan layanan kesehatan dan gizi dalam meningkatkan mutu layanan pembelajaran PAUD di posyandu Kabupaten Gorontalo. (2) mengetahui hambatan-hambatan yang dihadapi dalam penyellenggaraan PAUD yang terintegrasi dengan layanan kesehatan dan gizi dalam meningkatkan mutu layanan pembelajaran di posyandu di Kabupaten Gorontalo. Dan (3) mengetahui bagaimana mutu layanan pembelajaran dalam penyelenggaraan PAUD terintergasi layanan kesehatan dan gizi di posyandu kabupaten Gorontalo. Konsep yang dijadikan dasar dalam penelitian ini ialah hakikat PAUD holistik, hakikat posyandu, hakikat mutu pembelajaran, hakikat kesehatan dan gizi, dan karakteristik anak usia dini. Penelitian ini menggunakan pendekatan analisis-kualitatif, teknik pengumpulan data yang digunakan adalah pengamatan, dokumentasi dan wawancara yang dilakukan pada penyelenggaraan PAUD Terintegrasi. Teknik analisis data yang digunakan adalah teknik analisis deskriptif kulitatif. Hasil penelitian ini menunjukkan bahwa (1) Penyelenggaraan PAUD terintegrasi dengan layanan kesehatan dan gizi, bahwa dalam perencanaan, pelaksanan dan evaluasi telah dilaksanakan, (2) Hambatan yang ada baik eksternal maupun internal yang terjadi baik dari tutor pengolola, orang tua dari tutor sendiri adalah persoalan waktu misalnya ada pertemuan yang harus dihadiri sehingga proses pembelajaran tidak berjalan sesuai dengan telah direncanakan ,dan juga pembagian waktu yang harus dijadwalkan oleh pengolola dalam keterlibatannya pada pengololaan baik persoalan biaya maupun pemantauan pelaksanaan dan kehadiran orang tua dalam partisipasi baik pengusulan suatu rencana demi pengembangan Pos PAUD, dan (3) Mutu layanan pembelajaran dilihat dari perkembangan siswa baik dari segi perkembangan kognitif,bahasa sosial, moral, motorik maupun seni para tutor memiliki tanggungjawab yang baik. Berdasarkan data hasil penelitian faktor pendidikan dan pengalaman dapat meningkatkan kemampuan kader, kemudian kurangnya keterlibatan orang tua dalam partisipasi penyelenggraan PAUD terintegrasi lebih banyak mensosialisasikan demi peningkatannya sedangkan untuk mendapatkan fasilitas yang lebih memadai perlu pengelola menegosiasi bagi para pemerhati pendidikan.